Design of Web-Based After School Tutoring Information System ( Case Studies in "SiPintar" After School Tutoring Mantingan ) - Tri Suseno, Chandra, Umi Fadlillah, ST. MEng, Gunawan Ariyanto, Ph.D (2015)
Design of Web-Based After School Tutoring Information System (Case Studies in "SiPintar" After School Tutoring Mantingan) Chandra Tri Suseno, Umi Fadlillah, Gunawan Ariyanto Department of Informatics, Faculty of Communication and Informatics Muhammadiyah University of Surakarta Email: Chandra.ard@gmail.com Chandra Tri Suseno. L200102015 Design of Web-Based After School Tutoring Information System (Case Studies in "SiPintar" After School Tutoring Mantingan). Study Programs at the Department of Informatics, Faculty of Communication and Informatics Muhammadiyah University of Surakarta. This study aims to (1) Establish a media information website that can provide information to the public. (2) Building a website can do the management of information media student data accurately and precisely. (3) To assist and facilitate the process of monitoring the progress of student learning. Methods this study uses observers, interviews, and a literature method, this method for obtaining accuracy and validation of precise data, in order to get maximum results for the user. The results show the implementation of information media websites that can provide information to the public, the web pages were made in accordance with the design. Not only coding programs, web pages are also designed so that it looks attractive. In addition to the program administrator can edit, delete, and can add to the list of students who want value fed by name and subjects taken by students. The results of subsequent research, students and parents can access the value of the development and learning of students accessing material simply by entering your name and email address. Keywords: Design, Media Information, SiPintar, Web-Based